فاعلية التعليم الديني في تحصين فكر المجتمع من الغلو والتطرف - الجبوري, قصي سعيد احمد; المحمدي, عبد الرحمن احمد (Al-Adab Journal, 2019)
The importance of religious education lies in the formation of human personality, especially early education, which leaves clear traces in the human personality of thought and behavior.Extremism has become a phenomenon that has begun to spread in societies of all kinds, patterns and beliefs, and it is not related to any particular environment, community or religion.The subsequent stages of religious instruction may reinforce, refine, or refine the initial structures, whether they are intellectual or behavioral, which means that the subsequent stages are no less important than the initial educational stages and may be more serious if the appropriate climate exists.